Industrial Safety Management 21st Century Perspectives of Asia (Managing the Asian Century,, 2018)
This edited volume focuses on research conducted in the areas of industrial safety. Chapters are extensions of works presented at the International Conference on Management of Ergonomic Design, Industrial Safety and Healthcare Systems. The book addresses issues such as occupational safety, safety by design, safety analytics and safety management. It is a useful resource for students, researchers, industrial professionals and engineers.